UPAYA MENGIMPLEMENTASI WIBAWA PENEGAK HUKUM MELALUI PENEMUAN HUKUM - Soumena, M. Yasin (DIKTUM: Jurnal Syariah dan Hukum, 2011)
The existence of laws in the midst of society is to protect the interests of human beings that need to be enforced and implemented. In enforcement, often clash between fair and unfair, but all that is relative. Therefore, to fulfill a sense of justice, any rule of law made always comes with an explanation. However, once it was called the explanation, it often creates a new explanation for just described "pretty clear" the text of the law alone, so it still requires more explanation. Coupled with the rules that no longer fit with the demands of the times. This is where the legal discovery required by either law enforcement or interpretation of legal discovery freely outside the law. This way will give birth to the authority of law enforcement officials in the midst of society